Research on the Impact of Labyrinth Seal Ring Tooth Profile on the Pressure Pulsation of Leakage Chambers in High-Speed Centrifugal Pumps - Guodong Zhao; Jiahao Xu; Jie Lian; Yanpi Lin; Zuchao Zhu (Lubricants)
The gap seal ring is a critical component in high-speed centrifugal pumps. The leakage rate and performance of the pump are sensitive to variation in seal ring parameters. This study investigates the influence of seal ring tooth profile on the leakage flow of pump chambers. Numerical simulation and experimental tests are used to analyze the impact of four different tooth-height labyrinth seal ring structures on the pressure pulsation characteristics of pump leakage chambers. It can be concluded that the use of labyrinth seal rings can significantly reduce the pressure pulsation and leakage rate of pump chambers. For the Case 2 structure with a tooth height of 0.18 mm, the pressure pulsation in the pump chamber can be reduced by a maximum of 22.5%, and the leakage rate can be reduced by 41.1%. For the Case 3 structure with a tooth height of 0.23 mm, the pressure pulsation in the pump chamber can be reduced by a maximum of 30.3%, and the leakage rate can be reduced by 40.6%. The use of labyrinth seal rings significantly reduces the pressure pulsation intensity of the impeller surfaces, which improves the force stability of the high-speed centrifugal pump impeller. This study is helpful in providing theoretical support for the design of labyrinth seal rings in high-speed centrifugal pumps.